A newborn with coffin-siris syndrome - Cui, Liru; Jin, Xiaoli (Journal of the Pakistan Medical Association, 2023)
Coffin-Siris syndrome (CSS) is a rare congenital genetic syndrome, a multisystem disease related to congenital abnormalities, that manifests with abnormal features, causes repeated infections and is associated with developmental delays. Here, we report a newborn male with CSS from Baoding in the Hebei Province of China. Keywords: Coffin-Siris syndrome; newborn; rare disease.